Korelasi Faktor Demografi terhadap Kepercayaan Diri Menghadapi Pensiun Karyawan Padma Resort Legian - I Putu Esa Widaharthana; Ni Made Dwi Oktavianthi; Made Artajaya (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2020)
The main aim of the study is to analyze the correlation between demographic factors in determining the employee’s retirement confidence in hotel industry especially Padma Resort Legian. While the objectives of the study are to determine the relationship between demographic factors consist of gender, age, education, income and family dependent towards employee’s retirement confidence. The methods of collecting data is through the 98 questionnaires distribution to the pre-retiree employees from Housekeeping, Engineering and Food & Beverage Service and Product Department in Padma Resort Legian.. The techniques of analyzing data that used in this research are Crosstabs and Chi-Square test program. The findings of this research shows that two of demographic factors which are gender and age did not show any positive relationship with the retirement confidence. Otherwise, the three other factors which are income, education and family dependent show strong and positive relationship with the retirement confidence. The study also finds that income is the most important thing in building the retirement confidence of the employees.